(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper, we show new ways of proving the arithmetic-geometric mean AGM inequality through the first product and the second product inequalities. In addition, we prove the AGM inequality through the binomial inequalities. These methods are alternative ways of proving AGM inequalities.